Experiences and Challenges of Teachers in Handling Learners with Intellectual Disability During Covid-19 Pandemic (International Journal of Scientific Research and Management (IJSRM), 2024)
This study delved into the list of significant challenges that teachers were experiencing in handling ID learners. It employed a qualitative method in gathering data on teachers-participants’ experiences and challenges. A total of 20 teachers were selected using a convenient purposive sampling as the participants. The findings of this study revealed that teacher participants have observed and experienced multifaceted scenarios and difficulties during the COVID-19 pandemic. The data showed the existence of the challenges based on DepEd support, the lack of governmental provision of devices to aid learning, the limited learning experience, and instructional time that affect the learner’s personality, social orientations, and performance due to the absence of direct instruction. Likewise, the study concluded that the COVID-19 pandemic has affected and brought challenges to teachers and learners and has created the failure of support from the DepEd and the government. It conveyed the importance of parental support without the teacher’s direct instruction. Hence, it is recommended that schools enhance teacher training, prioritize face-to-face instruction, strengthen parental support, increase resource allocation, promote inclusive practices, and conduct further research on effective strategies.